Motivation and Constraints of the Ummahaat in Learning Arabic at Mahad Umar bin Khattab Muhammadiyah University Sidoarjo: Motivasi dan Kendala Para Ummahat dalam Pembelajaran Bahasa Arab di Mahad Umar Bin Al-Khattab Universitas Muhammadiyah Sidoarjo - Amini , Anzalna Rahmah; Hikmah, Khizanatul (Journal of Islamic and Muhammadiyah Studies, 2024)
Language is a communication tool to convey one's wishes to someone else around the world with various characteristics. Arabic is the second most widely used international language, in learning it there are several obstacles that most people experience. Among them is the age factor, which affects memory when receiving lessons, health, mood, tuition fees, signals (for those who are online), distance, besides that it is also a factor in dividing time between family, study and work. In order to overcome this, supporting factors such as strong motivation during the learning process are needed. This is experienced by the ummahat Mahad Umar Bin khattab Muhammadiyah University of Sidoarjo, their azzam to be able to return to study at a young age, the underlying motivation for the ummahat in learning Arabic is to understand the Al-Quran and translate it well, as a provision for communication, educating their children, job demands, as a filler in free time, motivating peers, and realizing the ideals of youth to study in college. Highlights: Age challenges: Memory decline, health issues, and time constraints pose hurdles for Arabic learners, especially older individuals. Motivation: Strong desire to understand the Quran, advance careers, and fulfill personal aspirations drives learners to overcome obstacles in Arabic language acquisition. Ummahat's role: Mothers from Mahad Umar Bin Khattab Muhammadiyah University display determination to learn Arabic despite challenges, balancing family, education, and personal growth. Keyword: Motivation, Constrain, Ummahat, Learning Arabic